Examining What Works for Youth With Moderate Risk Involved With the Juvenile Justice System: Comparing the Effect of the Community Connections Program and a Vocational Support Program Over a 9-Year Time Period - Espinosa, Erin M. (Criminal justice policy review, 2021)
Using administrative data from an urban juvenile probation department between January 2007 and August 2016, the study included youth who were placed on court-ordered postadjudication community supervision and who were deemed to have a moderate risk of reoffending by the department’s risk and needs assessment. The two programs evaluated include a vocational support program (VSP) and the Community Connections program (CC). Youth across both groups were matched using propensity score matching, creating a final sample of 301 individual youth per program. When examining the program effect of CC versus VSP across six time-to-event variables (i.e., time to second program, detention, out-of-home placement, another offense, violation of court order, and days in program), the findings were mixed. However, across both programs, analyses revealed youth with a successful discharge and longer time spent in their program had better outcomes.